IDF curved structures: Villa Olga and Santa Isabel waste treatment plants - municipality of Cúcuta - Colombia (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2007)
Through agreement No. 183/03 between the Institute of Hydrology, Meteorology, and Environmental Studies (IDEAM) and the University of Pamplona, they agreed to offer student internships and work placements, with IDEAM providing, through its Technical Archive and during the second semester of 2005, rainfall measurement reports. Unipamplona selected, evaluated, and processed the information using methodologies standardized by the World Meteorological Organization (WMO). The final product of these internships was the development of IDF curves for the Cinera-Villa Olga (N 07° 51' and W 72° 34') and Santa Isabel (N 8° 14', W72° 26') stations located in the municipality of Cúcuta, Department of Norte de Santander, Colombia.
Keywords: IDF curves; intensity; duration; frequency; precipitation; OMM; standardized methodology; Ciner station - Villa Olga; Santa Isabel station